Strong association between herpes simplex virus-1 and chemotherapy-induced oral mucositis in patients with hematologic malignancies - Hong, Junshik (Korean J Intern Med, 2020)
BACKGROUND/AIMS: A link between oral cavity infections and chemotherapy-induced oral mucositis (CIOM) in patients with hematological malignancies (HMs) undergoing intensive chemotherapy (IC) or hematopoietic stem cell transplantation (HSCT) has been suggested. However, conclusive data are lacking, and there are no current guidelines for the prophylactic use of antimicrobials to prevent CIOM in these populations. METHODS: The relationships between herpes simplex virus (HSV) reactivation and Candida colonization in the oral cavity and CIOM in patients with HMs undergoing IC or HSCT were evaluated. Patients aged ≥ 19 years with HMs undergoing IC or HSCT were enrolled. Each patient was evaluated for HSV and Candida in the oral cavity along with CIOM at baseline and during the 2nd, 3rd, and 4th weeks. RESULTS: Seventy presentations among 56 patients were analyzed. CIOM was observed in 23 presentations (32.9%), with a higher incidence associated with HSCT (17 of 35 presentations, 48.6%) than with IC (six of 35 presentations, 8.6%). The reactivation of HSV-1 was significantly associated with an increased incidence of CIOM after adjusting for age, sex, type of disease, and treatment stage. A higher HSV-1 viral load was associated with an increased incidence of CIOM. The presence of Candida was not associated with CIOM. CONCLUSIONS: HSV-1 reactivation in the oral cavity was highly associated with CIOM in patients with HMs undergoing high-dose chemotherapy.